The Slippery Ground of Turkish Foreign Policy: An Analysis of Foreign Policy Discourse of Political Parties in the Turkish Parliament: In the Case of the Eastern Mediterranean - Türkdoğan, Seyyide Sena; KOUROU, NUR SİNEM (6th Conference of the ECPR Standing Group on Parliaments, 2021)
There is an ongoing debate on the paradigm shift in Turkish foreign policy under the AKP rule, which has been characterized by Western-orientation and detachment from the pre-Republican imperial history. Although Turkish foreign policy is shaped under the leadership of AKP, the convergence and divergence among the other political parties in the Turkish Grand National Assembly are crucial to reflect the multifaceted nature of the foreign policy-making processes. In this paper, we intend to analyze the positions and treats of political parties in the parliament towards one of the heated debates in Turkish foreign policy: The Eastern Mediterranean. The dispute, rooted in crucial historical events in Turkish political life, has become the focus of many domestic and foreign policy actors. Based on Putnam’s two-level game approach, this study intends to reveal the first level of the foreign policy formation in Turkish politics through analyzing the political parties’ treats towards populism, nationalism, neo-Ottomanism, and liberal institutionalism. In order to track the patterns of the abovementioned dimensions, we have examined the speeches of the MP’s using R Studio and Nvivo programs; additionally, we interpreted the discourses of the party leaders. By doing so, we intend to show, on the one hand, the polarized context of Turkey has been observed in the foreign policy discourse of the political parties. On the other hand, how political parties, regardless of whether they are in government or opposition, share the mixture of the populist, nationalist and neo-Ottomanist, and liberal institutionalist inclination; however, their level varies to their positions in the political spectrum.
Keywords: Foreign Policy; Institutions; Nationalism; Parliaments; Political Parties; Populism; Religion; Mixed Methods